PENGARUH ROA, NPM, CR, DAN DER TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR PERHOTELAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Vinona Lula Putri Aprila (LPPM Universitas Bina Bangsa, 2024)
This research was conducted to determine the effect of Return On Assets (ROA), Net Profit Margin (NPM), Current Ratio (CR), and Debt to Equity Ratio (DER) on share prices in public sector companies listed on the Indonesia Stock Exchange (BEI). 2019-2022. The sampling method in this research was a purposive sampling method totaling 4 companies. This research uses multiple linear regression analysis with the help of SPSS 22 software. The results of this research show that the variables Return On Assets (ROA), Net Profit Margin (NPM), Current Ratio (CR), and Debt to Equity Ratio (DER) simultaneously influence to share prices. However, Return On Assets (ROA), Net Profit Margin (NPM), and Current Ratio (CR) partially have no effect on stock prices. Meanwhile, the Debt to Equity Ratio (DER) variable partially influences share prices